A Case–Control Study Investigating Simulated Driving Errors in Ischemic Stroke and Subarachnoid Hemorrhage - Hird, Megan A.; Vesely, Kristin A.; Tasneem, Tahira; Saposnik, Gustavo; Macdonald, R. Loch; Schweizer, Tom A. (Frontiers in Neurology, 2018)
Background: Stroke can affect a variety of cognitive, perceptual, and motor abilities that are important for safe driving. Results of studies assessing post-stroke driving ability are quite variable in the areas and degree of driving impairment among patients. This highlights the need to consider clinical characteristics, including stroke subtype, when assessing driving performance. Methods: We compared the simulated driving performance of 30 chronic stroke patients (>3 months), including 15 patients with ischemic stroke (IS) and 15 patients with subarachnoid hemorrhage (SAH), and 20 age-matched controls. A preliminary analysis was performed, subdividing IS patients into right (n = 8) and left (n= 6) hemispheric lesions and SAH patients into middle cerebral artery (MCA, n = 5) and anterior communicating artery (n = 6) territory. A secondary analysis was conducted to investigate the cognitive correlates of driving. Results: Nine patients (30%) exhibited impaired simulated driving performance, including four patients with IS (26.7%) and five patients with SAH (33.3%). Both patients with IS (2.3 vs. 0.3, U = 76, p<0.05) and SAH (1.5 vs. 0.3, U = 45, p<0.001) exhibited difficulty with lane maintenance (% distance out of lane) compared to controls. Additionally, patients with IS exhibited difficulty with speed maintenance (% distance over speed limit; 8.9 vs. 4.1, U = 81, p<0.05), whereas SAH patients exhibited difficulty with turning performance (total turning errors; 5.4 vs. 1.6, U = 39.5, p <0.001). The Trail Making Test (TMT) and Useful Field of View test (UFOV) were significantly associated with lane maintenance among patients with IS (rs >0.6, p<0.05). No cognitive tests showed utility amongst patients with SAH. Conclusions: Both IS and SAH exhibited difficulty with lane maintenance. Patients with IS additionally exhibited difficulty with speed maintenance, whereas SAH patients exhibited difficulty turning performance. Current results support the importance of differentiating between stroke subtypes and considering other important clinical characteristics (e.g. side of lesion, vascular territory) when assessing driving performance and reinforce the importance of physicians discussing driving safety with patients after stroke.